The Evolution of Social Norms in Common Property Resource Use - Sethi, Rajiv; Somanathan, E. (American Economic Review, 1996)
The problem of extracting commonly owned renewable resources is examined within an evolutionary-game-theoretic framework. It is shown that cooperative behavior guided by norms of restraint and punishment may be stable in a well-defined sense against invasion by narrowly self-interested behavior. The resource-stock dynamics are integrated with the evolutionary-game dynamics. Effects of changes in prices, technology, and social cohesion on extraction behavior and the long-run stock are analyzed. When threshold values of the parameters are crossed, social norms can break down leading generally to the lowering of the long-run stock, and possibly to its extinction.